Labor Demand in the Past, Present and Future - Georg Graetz (Center for Economic Studies and ifo Institute (CESifo), 2020)
Since the beginning of the Industrial Revolution, technological change has led to the automation of existing tasks and the creation of new ones, as well as the reallocation of labor across occupations and industries. These processes have been costly to individual workers, but labor demand has remained strong, and real wages have steadily increased in line with productivity growth. I provide evidence suggesting, however, that in recent decades automation has outpaced the creation of new tasks and thus the demand for labor has declined. There is strong disagreement about the future of labor demand, and predictions about technological breakthroughs have a poor track record. Given the importance of overall labor demand for workers' standard of living as well as their ability to adjust to a changing labor market, obtaining accurate forecasts should be a priority for policy makers.
Keywords: J23; O33; 330; automation; labor demand; labor share; technology; wages